Eksplorasi Analisis Kebutuhan Bahan Ajar Berbasis Citizen Science Project untuk Memberdayakan Keterampilan Kolaborasi Siswa pada Materi Sistem Pernapasan - Ainun, Nur Aisyah; Marzukah, Marzukah; Adnan, Adnan; Saleh, Andi Rahmat; Khalidatunnisa, Besse (Bioed : Jurnal Pendidikan Biologi, 2025)
This research focuses on analysing the needs of teaching materials with a Citizen Science Project (CSP) based approach for students, as a means of learning that follows the challenges of the 21st century, especially collaboration skills. The needs analysis was conducted at SMA Negeri 5 Makassar as many as 51 students in the even academic year 2024/2025. The purpose of this study was to determine students' needs for CSP-based materials to be developed to empower collaboration skills. The method used is qualitative descriptive method. The data collection technique used in this study was to conduct an initial student needs analysis. The research instruments used were student needs questionnaire and collaboration skills questionnaire. The data analysis used is reducing the data into specific tables to be presented descriptively. The results of initial observations found that students need CSP-based teaching materials and found that the low collaboration skills of students were 84.31% and as many as 49.02% of students stated the difficulty of respiratory system material in Biology lessons. Based on this, it is necessary to develop a CSP-based book that can empower collaboration skills in biology learning, especially respiratory system material in schools for student competence in realising the Golden Indonesia 2045.